Norwegian Scabies in Two Immune-Compromised Patients: A Case Report - Mahmoud RAHDAR; Sharif MARAGHI (Tehran University of Medical Sciences, 2019)
Norwegian scabies (hyperkeratosis scabies) is an acute form of skin disease seen in immune-compromised patients. This study aimed to describe two cases of Norwegian scabies from Ahvaz, southwest of Iran in 2015. Two patients included a 55 year old man with renal transplant history and a 49 yr old man with diabetic mellitus and autoimmune disease, complained of dermatitis lesions and itching with sever hyperkeratosis, several macula and papules on neck and armpits for one-month duration were referred to a Iran Zamin Medical Diagnostic Laboratory in Ahvaz, Southwestern Iran in 2015. Patients were referred for fungal examination. Scraping from the crusted lesions of skin and slide preparation with 20% KOH was done. Microscopic examination presented that huge infestation of Sarcoptes scabiei in all forms of parasite included adult female, nymph stage and eggs. One of the patients spouse was also infested by Sarcoptes and appeared mild clinical symptoms. The disease was diagnosed with Norwegian scabies and the patients were successfully treated with topical 5% permethrin ointment for two weeks continuously. Overall, Norwegian scabies should be considered in immune- compromised patients with contaminated areas.